ATTITUDE TOWARDS GREEN MEMEDIASI PENGARUH ENVIRONMENTAL CONCERN DAN GREEN PERCEIVED VALUE TERHADAP GREEN PURCHASE INTENTION (STUDI PENGGUNAAN TUMBLER STARBUCKS DI WILAYAH SARBAGITA BALI) - Dewi Pitaloka Cahyadi, Nyoman; Jaya Agung Widagda, I Gusti Ngurah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023, 2023)
This study aims to determine the effect of environmental concern and green perceived value on green purchase intention which is mediated by attitude towards green in tumbler products at Starbucks. This study used a purposive sampling technique, namely 180 respondents who live in SARBAGITA (Denpasar, Badung, Gianyar, and Tabanan). The data obtained were analyzed by descriptive analysis and Partial Least Square. The results of the study found that environmental concern and green perceived value had a positive and significant effect on attitude towards green and green purchase intention, attitude towards green had a positive and significant effect on green purchase intention, and attitude towards green partially mediated the relationship between environmental concern and green perceived value with green purchase intention. The practical implication of this research is that it can provide information for company managers in making marketing programs which at the same time can educate and provide information to customers about the benefits of using a Starbucks tumbler.